Adsorption of P-Nitrophenol Onto Partially Reduced Graphene Oxide: An Experimental and Theoretical Study. (June 2018) - Yang, Mengzhi; Wang, Meiling
This study investigated the adsorption process of p -nitrophenol ( p -NP) onto partially reduced graphene oxide (prGO) using both experiment and theoretical calculations. The maximum adsorption capacity of prGO at pH 6.0 and 293 K for p -NP was 29.94 mg g −1 which was significantly higher than previously reported using a metal-doped reduced graphene oxide composite. Systematic, comparative theoretical calculations were used to investigate the adsorption mechanism of p -NP onto graphene oxide, prGO and graphene nanosheet (GN). Calculations revealed three types of adsorption site and indicated that the adsorption force and sites were significantly affected by the quantity and type of oxygen-containing functional groups on the GN. The adsorption affinity was mainly derived from hydrogen bonds and π-π stacking which was further demonstrated by FTIR analysis. Due to its excellent adsorption performance, good recyclability and easy separation, prGO can be a promising adsorbent for the efficient elimination of p -NP from wastewater in the future.